A Systematic Review of the Comparison of Different Types of Card Sorting - Elinda Tchivi; Bibhya Sharma; Sione Paea (IEEE Access)
Card sorting is a commonly used technique to extract mental models from users in computer science, especially in the field of Human Computer Interaction (HCI) to structure and arrange the functionality or content of interactive systems. It is a well-liked and reasonably priced method for figuring out customer preferences and designing efficient information architecture. This systematic review aimed to provide a review of the existing literature examining the different card sorting techniques under the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Systematic reviews and meta-analyses were sought in electronic databases, encompassing studies that explored the different card sorting techniques. Fifty eligible reviews were identified based on the inclusion criteria, and relevant information was extracted from the review and qualitatively compiled. Findings show a clear understanding of how these card sorting can contribute to different classifications based on their individual characteristics or their strengths. The paper ends with the mention of a few problems identified from the systematic review so that researchers in this field may pick these open problems for future research and hence contribute to the growing literature on card sorting.